Peer Group Activities: A Comprehensive Approach to Reduce Speaking Anxiety in EFL Classrooms - Marlia Marlia (FOSTER: Journal of English Language Teaching, 2025)
This study examined how practical peer group activities helped Indonesian first-grade high school students improve their English speaking skills and reduce their speaking anxiety. Through an explanatory mixed-method research design, the study methodically investigated the linguistic and psychological effects of collaborative learning strategies in EFL situations at SMAN 13 Pangkep throughout the 2024–2025 academic year. After being randomly selected, forty-four students were split equally into two groups: the experimental group received set-up peer group interventions. In contrast, the control group proceeded to use conventional solo learning strategies. The multi-instrument methodology used validated anxiety questionnaires derived from the Psychological and Sociocultural Anxiety Scale (PSCAS), semi-structured interviews, structured classroom observations, and standardized speaking assessments to collect thorough quantitative and qualitative data. According to statistical analysis, the experimental group's mean anxiety levels decreased from 64.95 to 56.09, significantly improving compared to the control group's more modest fall from 64.86 to 60.54 (p=0.029). At the same time, the experimental group's mean performance scores increased from 49.36 to 65.90, which was a substantial improvement above the control group's from 46.33 to 56.18 (p=0.009). Qualitative data supported these statistical findings, as participants described peer group activities as helpful, engaging, and life-changing for their language learning process. The collaborative task division, mutual feedback, and knowledge sharing created a supportive environment that students especially enjoyed. These factors combined to lower anxiety and boost confidence in oral communication. Significant empirical evidence is presented in the study to support the incorporation of organized collaborative learning practices as a successful educational intervention for addressing the complex relations between social, emotional, and psychological aspects that affect language acquisition. These results provide essential information for developing curricula and instructional strategies that build communicative competence and reduce language anxiety in teenage EFL learners in Indonesian classrooms.